EARLY STEPS OF TOMATO BREEDING RESIST TO ROOT-KNOT NEMATODE - Rudi Hari Murti; Fardatun Muamiroh; Tata Rina Wahyu Pujiati; Siwi Indarti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
The inheritance pattern of resistant tomato to root-knot nematode was studied. GM2 accession and Gondol Putih (GP) cultivars were used as resistant and susceptible parent, respectively. Parental plants, F1 generation, and the F2 generation were grown individually in the sterile soil. One thousand of larvae stage 2 (L2) nematode of M. incognita was infested in each plant. Data of root gall intensity, the number of egg mass, population of L2 nematodes in root and soil were analyzed with the Kormogorov-Smirnov’s test, Chi-square test, and potence ratio. The F2 selected resistant plants then were grown and self fertilized to identify of homozygote plants (F2) related to nematode resistant and good fruit characters. The result showed that the resistant to root-knot nematode was controlled by a dominant gene. Positive correlation between damage levels of roots, eggs mass number and L2 larvae population in the root was significant. Eleven selected plants, conferred the homozygous resistant gene, was prospective lines to be used pedigree or single seed descent selection in producing variety with resistant to nematode, high yield and quality of fruit. Keywords: tomato, root-knot nematode, resistant gene, dominant, homozygous, correlation